The role of resource limitation in restoration of sagebrush ecosystems dominated by cheatgrass (Bromus tectorum) - Jones, Rachel O; Chambers, Jeanne C; Board, David I; Johnson, Dale W; Blank, Robert R (Ecosphere (Washington, D.C), 2015)
Success of invasive annual grasses is often linked to increases in resources, and restoration ecologists have suggested that decreasing nitrogen (N) availability and restoring more conservative N cycles with lower N turnover should decrease the competitive advantage of these invaders and facilitate establishment of native perennials. We developed a multivariate conceptual model of the likely effects of environmental factors (precipitation and temperature) and potential management treatments (repeated burning, litter manipulation, and seeding an annual competitor) on soil N availability and success of cheatgrass, the most widespread invader in the western United States. We examined effects of the treatments in a five year field study in a cold desert shrubland. We used generalized linear mixed-effects models to examine differences among treatments over time, and structural equation modeling (SEM) to evaluate component hypotheses of the conceptual model. We hypothesized that burning would result in a pulse in soil available N due to heat-induced soil organic matter denaturation, but that subsequent fires would volatilize soil and biomass N resulting in progressive N deficiency. However, soil available N in burned plots was never lower than pre-burn levels, likely because burn temperatures were too cool to volatilize N from soils or aboveground biomass. Repeated burning decreased litter biomass, but there were generally no differences in soil available N between litter intact and litter removed plots. Litter removal had a negative effect on cheatgrass success likely due to effects on seed entrapment and plant establishment rather than N mineralization. Plots seeded with wheat generally had the lowest cheatgrass success, but available N was similar to other treatments, and decreased cheatgrass success was likely due to competition for other soil nutrients or water and reduced litter. In this semi-arid shrubland, long-term trends in available soil N and cheatgrass success were most strongly associated with precipitation and winter minimum temperatures. Treatments did not result in longer-term decreases in soil N, but indicated that integrated restoration approaches that reduce litter and seed banks and increase competitive interactions may be effective at reducing cheatgrass success and facilitating establishment of natives.